Prevalence of immunoglobulin G and M to SARS-CoV-2 and other human coronaviruses in The Democratic Republic of Congo, Sierra Leone, and Uganda: A longitudinal study. (June 2023) - Lawal, Bolarinde J.; Gallagher, Katherine E.; Kitonsa, Jonathan; Tindanbil, Daniel; Kasonia, Kambale; Drammeh, Abdoulie; Lowe, Brett; Mukadi-Bamuleka, Daniel; Patterson, Catriona; Greenwood, Brian; Samai, Mohamed; Leigh, Bailah; et al.
Highlights: We found a high prevalence of SARS-CoV-2 receptor binding-domain/nucleocapsid protein binding antibody (IgG/IgM) in the three settings in 2021. Almost all participants had seroconverted to SARS-CoV-2 by the end of 4 months of follow-up. Baseline IgG to endemic coronaviruses did not reduce the acquisition of SARS-CoV-2. Baseline IgG in SARS-CoV-2 predicted higher responses to COVID-19 vaccination. Abstract: Objectives: We assessed the prevalence of immunoglobulin G (IgG) and IgM against four endemic human coronaviruses and two SARS-CoV-2 antigens among vaccinated and unvaccinated staff at health care centers in Uganda, Sierra Leone, and the Democratic Republic of Congo. Methods: The government health facility staff who had patient contact in Goma (Democratic Republic of Congo), Kambia District (Sierra Leone), and Masaka District (Uganda) were enrolled. Questionnaires and blood samples were collected at three time points over 4 months. Blood samples were analyzed with the Luminex MAGPIX Ⓡ . Results: Among unvaccinated participants, the prevalence of IgG/IgM antibodies against SARS-CoV-2 receptor-binding domain or nucleocapsid protein at enrollment was 70% in Goma (138 of 196), 89% in Kambia (112 of 126), and 89% in Masaka (190 of 213). The IgG responses against endemic human coronaviruses at baseline were not associated with SARS-CoV-2 sero-acquisition during follow-up. Among the vaccinated participants, those who had evidence of SARS-CoV-2 IgG/IgM at baseline tended to have higher IgG responses to vaccination than those who were SARS-CoV-2 seronegative at baseline, controlling for the time of sample collection since vaccination. Conclusion: The high levels of natural immunity and hybrid immunity should be incorporated into both vaccination policies and prediction models of the impact of subsequent waves of infection in these settings.